Sensitivity of turbulent Schmidt number and turbulence model to simulations of jets in crossflow. (August 2016) - Valero, Daniel; Bung, Daniel B.
Abstract: Environmental discharges have been traditionally designed by means of cost-intensive and time-consuming experimental studies. Some extensively validated models based on an integral approach have been often employed for water quality problems, as recommended by USEPA (i.e.: CORMIX). In this study, FLOW-3D is employed for a full 3D RANS modelling of two turbulent jet-to-crossflow cases, including free surface jet impingement. Results are compared to both physical modelling and CORMIX to better assess model performance. Turbulence measurements have been collected for a better understanding of turbulent diffusion's parameter sensitivity. Although both studied models are generally able to reproduce jet trajectory, jet separation downstream of the impingement has been reproduced only by RANS modelling. Additionally, concentrations are better reproduced by FLOW-3D when the proper turbulent Schmidt number is used. This study provides a recommendation on the selection of the turbulence model and the turbulent Schmidt number for future outfall structures design studies. Highlights: Accuracy assessment of FLOW-3D and CORMIX for 3D modelling of complex environmental discharges. RNG k − ε and k − ω turbulence model performance analysis for a jet to crossflow study including free surface impingement. Sensitivity analysis of turbulent Schmidt number for contaminant modelling with RANS equations. High-speed camera analysis of Zone of Flow Establishment and usage of imaging techniques.